INTROGRESSIVE HYBRIDIZATION BETWEEN RHODODENDRON KIUSIANUM AND R. KAEMPFERI (ERICACEAE) IN KYUSHU, JAPAN BASED ON CHLOROPLAST DNA MARKERS - Kobayashi, N.; Handa, T.; Miyajima, I.; Arisumi, K.; Takayanagi, K. (Edinburgh Journal of Botany, 2007)
Wild evergreen azalea populations of Rhododendron kiusianum and R. kaempferi (Ericaceae) were analysed using a chloroplast DNA (cpDNA) PCR-RFLP marker that was used to detect introgressive hybridization in our previous study of the Kirishima Mts populations.The populations of the intermediate region in the Unzen Mts, which show phenotypic variation, were demonstrated to result from interspecific hybridization between Rhododendron kiusianum and R. kaempferi, possessing cpDNA from either R. kiusianum (1030/420 bp) or R. kaempferi (950/420/80 bp).Most individuals of Rhododendron kiusianum in the Kujyu Mts, the Aso Mts and the surrounding mountains exhibited the PCR-RFLP pattern of R. kaempferi. These results from the Kujyu Mts and the Aso Mts indicate that natural hybridization and cytoplasmic introgression from Rhododendron kaempferi to R. kiusianum have occurred in the relatively distant past. In the case of Mt Yufudake and Mt Haneyama, the Rhododendron kiusianum population retains the effects of natural hybridization with R. kaempferi in the cpDNA as well as in the variation in flower characteristics.All individuals of Rhododendron kiusianum on Mt Onogaradake in the Takakuma Mts exhibit R. kiusianum cpDNA (1030/420 bp), in spite of variation in flower colour.